Which expressions are equivalent to 12x - 6?

B and E
A) It's wrong because
[tex] - 6 \times (2x - 1) = - 12x + 6[/tex]
B) It's right because
[tex]6 \times (2x - 1) = 12x - 6[/tex]
C) It's wrong because
[tex]6x \times (2 - 1) = 6x \times 1 = 6x[/tex]
D) It's wrong because
[tex] - 6x \times (2x - 1) = - 12 {x}^{2} + 6[/tex]
E) It's right because
[tex] - 6 \times ( - 2x + 1) = 12x - 6[/tex]
F) It's wrong because
[tex]6 \times ( - 2x + 1) = - 12x + 6[/tex]
Equivalent expression are the expression in which the resultant value of the expression are same but the way of represent ion is different.The expression which are equivalent to the given expression are[tex]6(2x-1)[/tex] and [tex]-6(-2x+1)[/tex]. Thus the option B and Option E are correct.
The given expression in the problem is,
[tex]12x-6[/tex]
Equivalent expression are the expression in which the resultant value of the expression are same but the way of represent ion is different
Check all the option,
[tex]-6(2x-1)[/tex]
Let [tex]f(x)[/tex] is the given expression. Thus,
[tex]f(x)=-6(2x-1)[/tex]
[tex]f(x)=-12x+6[/tex]
The result is not equal to the given expression. Thus option A is not correct.
[tex]6(2x-1)[/tex]
Let [tex]f(x)[/tex] is the given expression. Thus,
[tex]f(x)=6(2x-1)[/tex]
[tex]f(x)=12x-6[/tex]
The result is equal to the given expression. Thus option B is correct.
[tex]6x(2-1)[/tex]
Let [tex]f(x)[/tex] is the given expression. Thus,
[tex]f(x)=6x(2-1)[/tex]
[tex]f(x)=6x(1)[/tex]
[tex]f(x)=6x[/tex]
The result is not equal to the given expression. Thus option C is not correct.
[tex]-6x(2x-1)[/tex]
Let [tex]f(x)[/tex] is the given expression. Thus,
[tex]f(x)=-6x(2x-1)[/tex]
[tex]f(x)=-12x^2+6[/tex]
The result is not equal to the given expression. Thus option D is not correct.
[tex]-6(-2x+1)[/tex]
Let [tex]f(x)[/tex] is the given expression. Thus,
[tex]f(x)=-6(-2x+1)[/tex]
[tex]f(x)=12x-6[/tex]
The result is equal to the given expression. Thus option E is correct.
[tex]6(-2x+1)[/tex]
Let [tex]f(x)[/tex] is the given expression. Thus,
[tex]f(x)=6(-2x+1)[/tex]
[tex]f(x)=-12x+6[/tex]
The result is not equal to the given expression. Thus option F is not correct.
Thus the expression which are equivalent to the given expression are[tex]6(2x-1)[/tex] and [tex]-6(-2x+1)[/tex]. Thus the option B and Option E are correct.
https://brainly.com/question/10628562